Perancangan Strategi Peningkatan Service Quality Terhadap Kepuasan Pelanggan dengan Metode Importance Performance Analysis dan Quality Function Deployment Pada Gramedia Cabang Teuku Umar Bali - Dwi Satya Putra Kencana; Mia Juliana; Bryan Estavan Imanuel Sitanggang (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
The aspect of service quality is an important thing to consider to maintain business continuity. Based on the importance of services provided to customers, Gramedia must really pay attention to its services. Based on the assessment results through the Google Review Application, several aspects are still complained about by customers, indicated by a low rate. Low ratings can potentially influence other customers. This research was conducted to measure the Customer Satisfaction Index (CSI) of Gramedia customers, followed by identifying Service Quality attributes that are important to improve using the Importance Performance Analysis (IPA) and Quality Function Deployment (QFD) methods. The results of the analysis obtained a CSI value of 72.96% in the range of 100%. This indicates the need to improve service quality with 5 attributes that must be prioritised for improvement. Based on the analysis of the Quality Function Deployment (QFD) method, namely the development of other supporting facilities such as playgrounds and reading rooms containing chairs and tables, adjusting and making parking system standards in collaboration with vendors, completing books and stationery equipment according to customer needs, using the latest e-catalog technology in service services, providing training for employees, and installing room layout information.